2021
DOI: 10.1016/j.amsu.2021.102515
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on Caribbean Medical Students: A cross-sectional study

Abstract: The COVID-19 pandemic has introduced a wide range of challenges to numerous institutions around the world. One of these vital programs being affected is Caribbean medical schools. To continue to train future physicians, Caribbean medical schools have been forced to deliver lectures through video chat, delaying clinical training years as well as exams. Reveal current shortcomings in medical education to improve future learning strategies based on student perspectives. To further explore the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…It should inform policymakers in academia to reflect on the psychological needs of students in virtual teaching environments (Shah et al, 2021). In addition to this, students also often pay less attention when online classes occur (Thind et al, 2021). So, during the covid-19 pandemic, educators must understand the desires and perspectives of students towards online learning.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…It should inform policymakers in academia to reflect on the psychological needs of students in virtual teaching environments (Shah et al, 2021). In addition to this, students also often pay less attention when online classes occur (Thind et al, 2021). So, during the covid-19 pandemic, educators must understand the desires and perspectives of students towards online learning.…”
Section: Findings and Discussionmentioning
confidence: 99%
“… 8 , 9 A Libyan study that investigated over 3000 medical students' experiences of the pandemic found that students paid less attention during online lectures. 10 Issues of Zoom burnout and Zoom fatigue have also been recently raised, caused by the need for attentiveness to nonverbal cues and the constant awareness of what a person is doing while the Zoom camera is on. 11 The systematic review of 10 studies on medical student support systems during the COVID‐19 pandemic emphasised the importance of a safe learning environment online, as well as the need for educational institutions to conduct precise evaluation of the changes made in response to the pandemic, as opposed to merely describing the positive effects of the changed programmes.…”
Section: Introductionmentioning
confidence: 99%
“…While this transition has been a blessing in many ways, such as enabling continuation of training, it also has some pitfalls including reduced collaborative learning, feelings of distress for tutors associated with diminished feedback when students' cameras are switched off, and challenges in building rapport with patients during clinical encounters 8,9 . A Libyan study that investigated over 3000 medical students' experiences of the pandemic found that students paid less attention during online lectures 10 . Issues of Zoom burnout and Zoom fatigue have also been recently raised, caused by the need for attentiveness to nonverbal cues and the constant awareness of what a person is doing while the Zoom camera is on 11 …”
Section: Introductionmentioning
confidence: 99%
“…Other studies evaluated students' preferences (but not efficacy) for online vs offline learning while others investigated the general impact of the COVID-19 pandemic on medical education. A cross-sectional study, conducted from February 2021 to April 2021 via social media on second, third, and fourth-year medical students of six Caribbean medical schools (including our institution, AUACOM), revealed that over 60% of the students preferred offline F2F teaching modality over online learning [ 18 ]. Most students reported being less time efficient and paying less attention during online lectures.…”
Section: Discussionmentioning
confidence: 99%